Comparisons of Outcomes of Real-World Patients With Advanced Pancreatic Cancer Treated With FOLFIRINOX Versus Gemcitabine and Nab-Paclitaxel: A Population-Based Cohort Study. Issue 7 (August 2019) - Papneja, Neha; Zaidi, Adnan; Chalchal, Haji; Moser, Michael; Tan, Kiat; Olson, Colleen; Haider, Kamal; Shaw, John; Ahmed, Shahid
Abstract : Objectives: The aim of this study was to compare the efficacy and safety of FOLFIRINOX (5-FU/leucovorin, irinotecan, and oxaliplatin) and gemcitabine/nab-paclitaxel (GnP) in patients with advanced pancreatic cancer. Methods: Patients with newly diagnosed advanced pancreatic cancer in Saskatchewan, Canada, from 2011 to 2016, who received FOLFIRINOX or GnP were assessed. A Cox proportional multivariate analysis was performed to evaluate prognostic variables. Results: One hundred nineteen eligible patients with median age of 61 years and male/female ratio of 70:49 were identified. Seventy-seven percent had metastatic disease. Of 119 patients, 86 (72%) received FOLFIRINOX and 33 (28%) were treated with GnP. Median progression-free survival of the FOLFIRINOX group was 6.0 months [95% confidence interval (CI), 4.5–7.5] versus 4.0 months (95% CI, 2.9–5.1) with GnP ( P = 0.39). The median overall survival of the FOLFIRINOX group was 9.0 months (95% CI, 7–11) compared with 9.0 months (95% CI, 4.2–13.8) with GnP ( P = 0.88). On multivariate analysis, albumin [hazard ratio (HR), 0.63; 95% CI, 0.41–0.97], male sex (HR, 0.65; 95% CI, 0.43–0.97), and second-line therapy (HR, 0.50; 95% CI, 0.28–0.86) were correlated with survival. Conclusions: Our results showed that real-world patients with advanced pancreatic cancer treated with FOLFIIRNOX or GnP had comparable survival with different safety profile.